Bone in intestinal polyp-a curious observation - Bhawna, JB; Datta, S; Mukherjee, S; Banerjee, U (Bangladesh Journal of Medical Science, 2013)
We report rare phenomena of ossification in benign colon polyp. An adult woman presented with occasional bleeding per rectum for which she was investigated. A polypoid rectal swelling was detected and histolopathology revealed an inflammatory polyp with osteoid formation. The case is presented for its rarity and available literature is reviewed. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16669 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 453-455